23.4k views
1 vote
How to factor g2 − 32g + 256

User Dcpartners
by
5.6k points

2 Answers

5 votes

Answer:


(g-16)^2

Explanation:


g^2-32g + 256

To factor it you should remember that


(a-b)^2 = a^2 -2ab+b^2

It is easy to seee that


32 = 2 \cdot 16

and


256 = 16^2

Therefore


g^2-32g + 256 = g^2 - (2\cdot 16)g+ 16^2 = (g-16)^2

User Heimy
by
5.0k points
1 vote

Answer:

Using the snowflake method, you have to find the factors of 256 that add up to get 32.

The result will look like this:

(g-16)(g-16)

User Agillgilla
by
4.6k points